GAMBARAN PERILAKU AGRESIF ANAK USIA 4-6 TAHUN DI TK BHAYANGKARI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Roslaini, Roslaini; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is still contained from aggressive behavior in children who are still prominent. The role of the family has enormous influence in shaping the personality of the child so that the child develops into a strong personal self-confidence, initiative, ambition, emotion stable, responsible, able to establish positive interpersonal relationships and others. The personality can be developed within the family. Therefore, researchers make improvements and optimize the aggressive behavior of children according to age development level. The purpose of the implementation of this research is to find a picture for aggressive behavior of children aged 4-6 years in kindergarten Bhayangkari District of Bangko Rokan Hilir. This type of research is descriptive method with quantitative approach. The number of samples in this study were 40 children consisted of 21 boys and 19 girls.Based on the analysis of the results of the assessment process in the overall field of indicators of physical aggression to obtain an average percentage of 78.06% with high criteria. On the verbal aggressiveness indicator average percentage of 87.12% is obtained with very high criteria and indicators that third gained an average percentage of 96.37% with the criteria of "never".Based on the results achieved from three indicator can be concluded that the aggressive behavior of children aged 4-6 years in kindergarten Bhayangkari District of Bangko not obtrusive and do not appoint aggressive behavior deviant. Aggressive behavior of children can still be controlled by the teacher well.Keywords: Aggressive, description of Conduct, 4-6 Year Olds.